Ferramentas para licenciamento paramétrico de projetos de empreendimentos habitacionais de interesse social - Maselli, Luccas Zambon (2021)
Technical standards and legislation constitute and regulate part of the housing development licensing process. Checking the conformity of new real estate projects against the legal reference values is a complex task. In this sense, the automation of this process, using computational resources, has the potential to make it more efficient. The automated compliance checking, digitally implemented, is a possible way to assist in the agility of licensing of housing developments, ensuring efficiency, objectivity, and transparency. Still, public procedures that include popular participation are ineffective and have a low adhesion rate by civil society. This dissertation aims to develop computational tools that help verify the legal parameters involved in the licensing procedures for housing developments. The proposals are divided into two fronts, aimed at popular participation and verifying requirements in geospatial models. For this, a consultative tool was developed for the population, using the Python language, in addition to a plugin for Geographic Information Systems (GIS) platform, where both are responsible for the parametric verification of housing developments. For application purposes, the city of São Carlos (SP – Brazil), and the urbanistic parameters present in its Master Plan, were used. The tool developed for public consultation operates from the insertion of primary project data, frequently found in Neighborhood Impact Studies, allowing the calculation of the coefficients applicable to the licensing process and generating a structured report of conformities and non-conformities. The geospatial tool, in turn, operates from the zoning and project’s vectorial data, and automatically calculates the applicable urban coefficients, comparing them with the reference values, where, in the end, it also generates a structured report. The application of such tools represents a breakthrough in fields that are still not very efficient, such as the popular participation in decision making and the housing licensing process itself, in addition to areas that have not been much explored, such as parametric verification on the GIS platform. The application of the tools can represent new paradigms in urban planning models since many operations performed manually can be rethought based on computational concepts. Also, the tools can integrate civil society into decision-making processes about the city and allow geospatial analysis based on the implementation of new housing developments.